Effects of a horizontal magnetic field on unstable vibration and noise of a friction interface with different magnetic properties. (April 2018) - Xu, J.Y.; Mo, J.L.; Wang, X.C.; Zhang, X.; Wang, D.W.; Zhou, Z.R.
Abstract: An experimental investigation studying the effects of a magnetic field on vibration and noise that occur when using a ball-on-disc friction system is described. Three types of friction pairs are introduced. The results show that a magnetic field can significantly reduce the friction noise, the corresponding vibration acceleration, and friction coefficient, for a steel–forged steel pair. However, the effects of magnetic field on the vibration and noise for other two friction pairs are limited. Moreover, a physical explanation is provided to describe the phenomenon, where the magnetic field attracts ferromagnetic wear debris, and cleans the wear trace. The major finding is that the noise reduction mechanism elicited by using a magnetic field can have extensive applicability in different fields. Highlights: The impact of magnetic field on friction-induced noise and vibration is evaluated. Contrast test is designed to verify the ability of magnet in reducing noise. The ability of magnet in cleaning wear debris and its effect on noise is studied. A noise reduction mechanism for magnetic field is proposed.